An aseismic slip transient on the North Anatolian Fault. Issue 7 (14th April 2016) - Rousset, Baptiste; Jolivet, Romain; Simons, Mark; Lasserre, Cécile; Riel, Bryan; Milillo, Pietro; Çakir, Ziyadin; Renard, François
Abstract: Constellations of Synthetic Aperture Radar (SAR) satellites with short repeat time acquisitions allow exploration of active faults behavior with unprecedented temporal resolution. Along the North Anatolian Fault (NAF) in Turkey, an 80 km long section has been creeping at least since the 1944, M w 7.3 earthquake near Ismetpasa, with a current Interferometric Synthetic Aperture Radar (InSAR)‐derived average creep rate of 8 ± 3 mm/yr (i.e., a third of the NAF long‐term slip rate). We use a dense set of SAR images acquired by the COSMO‐SkyMed constellation to quantify the spatial distribution and temporal evolution of creep over 1 year. We identify a major burst of aseismic slip spanning 31 days with a maximum slip of 2 cm, between the surface and 4 km depth. This result shows that fault creep along this section of the NAF does not occur at a steady rate as previously thought, highlighting a need to revise our understanding of the underlying fault mechanics. Key Points: A 1 month transient event ( Mw 5.3) has been detected by high temporal resolution InSAR time series along the North Anatolian Fault A Bayesian inversion constrains the depth (between 0 and 3 km), the length (8 km), and the peak slip (2 cm) of this transient event A need for a revision of the current mechanical model of this segment is highlighted